2004
DOI: 10.1111/j.1469-8749.2004.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual search in school‐aged children with unilateral brain lesions

Abstract: In this preliminary study, visual search for targets within and beyond the initial field of view was investigated in seven school‐aged children (five females, two males; mean age at testing 8 years 10 months, SD1 year 3 months; range 6 to 10 years) with various acquired, postnatal, focal brain injuries (haematoma, haemorrhage, meningioma, neuroblastoma, and cerebral abscess) in anterior or posterior sites of the left or right hemisphere, and seven control children (matched for age and sex) were also studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Difficulties in visual exploration/visual search have already been reported by previous authors (Fazzi et al, 2007; Netelenbos & Van Rooij, 2004; Salati et al, 2002). Children with these abnormalities typically need more time to search through a stimulus template and are more likely to neglect stimuli.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Difficulties in visual exploration/visual search have already been reported by previous authors (Fazzi et al, 2007; Netelenbos & Van Rooij, 2004; Salati et al, 2002). Children with these abnormalities typically need more time to search through a stimulus template and are more likely to neglect stimuli.…”
Section: Introductionsupporting
confidence: 71%
“…Difficulties with global visual perception (overview) and visual search have been frequently reported in CVI (Fazzi et al, 2007; Netelenbos & Van Rooij, 2004; Salati et al, 2002; Zihl & Dutton, 2015, p. 92). These difficulties may be interpreted in terms of impaired parallel visual processing and spatial integration, resulting in a restriction of the field of attention, which is also a characteristic feature of (mild) Balint syndrome (Philip et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Is visual search differentially affected in individuals with early damage to the visual system? Few studies have explored the effects of brain lesions acquired during childhood on visual search abilities, inconsistently reporting slower search responses in the contralesional visual field 96,97 . Other studies showed that patients who underwent hemispherectomy at 7 years of age or earlier showed greater sparing of visual orienting abilities compared with patients who underwent surgery at 17 years of age 98 .…”
Section: Brain Damage and Unconscious Visual Perceptionmentioning
confidence: 99%